2013
DOI: 10.1111/apt.12234
|View full text |Cite
|
Sign up to set email alerts
|

Associations of chronic hepatitis C with metabolic and cardiac outcomes

Abstract: SUMMARY BackgroundChronic hepatitis C virus (CH-C) infection is associated with metabolic conditions such as insulin resistance and type 2 diabetes (DM) and may increase the risk of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
133
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 31 publications
2
133
2
2
Order By: Relevance
“…15,16,37 The relative impact of the observed increase in LDL concentration associated with HCV clearance, shown here and in other studies, with the decrease observed in other biomarkers of cardiovascular disease observed with HCV clearance on subsequent risk for cardiovascular events requires prospective evaluation. 38 We also demonstrate that an LDL increase occurs with slower kinetics than the decline in HCV viral load in serum during treatment (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…15,16,37 The relative impact of the observed increase in LDL concentration associated with HCV clearance, shown here and in other studies, with the decrease observed in other biomarkers of cardiovascular disease observed with HCV clearance on subsequent risk for cardiovascular events requires prospective evaluation. 38 We also demonstrate that an LDL increase occurs with slower kinetics than the decline in HCV viral load in serum during treatment (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…15,16 HCV modulation of serum cholesterol is in part related to viral intrahepatic modulation of cholesterol biosynthesis, and HCV circulates with host lipoproteins in complexes termed lipoviral particles. 14,[17][18][19][20][21][22] While HCV genotype-3 (GT3) is notable for inducing hepatic steatosis and having the most marked reduction of serum lowdensity lipoprotein (LDL) among the HCV genotypes, infection with HCV GT1, the most common genotype in the United States, is also associated with insulin resistance and altered LDL concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Furthermore, it is involved in the development of insulin resistance and accelerates fibrosis progression, as well as can lead to advanced liver disease and hepatocellular carcinoma and raises mortality. 4,[7][8][9] Historically, peginterferon-alpha plus ribavirin has been the established treatment for GT-3 patients, which has led to sustained virologic responses in 70% to 80% of patients. 4,[10][11][12][13] Fibrosis or cirrhosis were predictive of reduced sustained virologic response; therefore, GT-3 patients with cirrhosis were especially hard to treat.…”
Section: Introductionmentioning
confidence: 99%
“…4%) in patients with HCV infection than in those with other forms of chronic hepatitis. [12][13][14][15] CLD and type 2 diabetes mellitus are two chronic conditions which contribute to a significant morbidity and mortality. Literature is scarce regarding the occurrence of type 2 diabetes mellitus in CLD in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%